2003
DOI: 10.1046/j.1365-2958.2003.03656.x
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline‐aptamer‐mediated translational regulation in yeast

Abstract: SummaryWe describe post-transcriptional gene regulation in yeast based on direct RNA-ligand interaction. Tetracycline-dependent translational regulation could be imposed via specific aptamers inserted at two different positions in the 5 ¢ ¢ ¢ ¢ untranslated region (5 ¢ ¢ ¢ ¢ UTR). Translation in vivo was suppressed up to ninefold upon addition of tetracycline. Repression via an aptamer located near the start codon (cap-distal) in the 5 ¢ ¢ ¢ ¢ UTR was more effective than repression via a capproximal position. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 49 publications
1
84
0
Order By: Relevance
“…However, there are only a few aptamers that have been reported that act as a riboswitch in vivo (Werstuck and Green 1998;Grate and Wilson 2001;Harvey et al 2002;Hanson et al 2003). In a previous study, we have shown that only 1 of 15 different tetracycline-binding aptamers is able to mediate ligand-dependent regulation of gene expression .…”
Section: Combining In Vitro Selection and In Vivo Screening Creates Amentioning
confidence: 95%
“…However, there are only a few aptamers that have been reported that act as a riboswitch in vivo (Werstuck and Green 1998;Grate and Wilson 2001;Harvey et al 2002;Hanson et al 2003). In a previous study, we have shown that only 1 of 15 different tetracycline-binding aptamers is able to mediate ligand-dependent regulation of gene expression .…”
Section: Combining In Vitro Selection and In Vivo Screening Creates Amentioning
confidence: 95%
“…489 Translational control elements based on tetracycline and theophylline-controlled aptamer have been realized in yeast. [490][491][492] In these studies, the potential of aptamer/ligand interactions to suppress translation was demonstrated using reporter genes ( Figure 21). …”
Section: Artificial Riboswitchesmentioning
confidence: 99%
“…In addition, we tested GC content effects by designing fourh airpins that maintained ap redicted thermal stability near ÿ 30 kcal/mol and a+ 4 position. Insert lengths were maintained using CAA motifs as spacers, since these motifs are presumed to have no secondary structure (Hanson et al 2003). We finally cloned control constructs composed entirely of CAA motifs for normalization to ''structure-lessR NAs''.…”
Section: Translation Reporter Systemmentioning
confidence: 99%